Use of stem cells from deciduous teeth in bone regeneration for the treatment of cleft lip and palate: A review of in vivo studies (Revista da Faculdade de Odontologia - UPF, 2024)
Objective: This study aimed to review in vivo studies on the use of stem cells derived from exfoliated deciduous teeth (SHED) for bone regeneration, particularly in the treatment of cleft lip and/or palate (CL/P). Methodology: The review followed PRISMA guidelines and included studies from PubMed, Scopus, and Google Scholar databases, published in the last 10 years in English, Spanish, or Portuguese. Strict inclusion and exclusion criteria were applied, focusing on in vivo studies using SHED for CL/P treatment. Keywords such as “Bone Regeneration,” “Tissue Engineering,” and “SHED” were used for the search. After screening 1,045 records and excluding duplicates, 7 studies were selected for full review. Results: The review identified 7 relevant studies, 6 of which were in vivo animal studies, and 1 was a clinical case report. These studies demonstrated that SHEDs effectively promoted bone regeneration, presenting a less invasive and promising alternative to traditional bone grafting techniques. Conclusion: SHEDs show significant potential in bone regeneration, offering a less invasive treatment option with fewer complications compared to autogenous bone grafts. However, more research is needed to address long-term safety, tumorigenesis, and optimal clinical applications before widespread clinical adoption.